Zachowania informacyjne czeskich i słowackich studentów w czasie pandemii COVID-19 z naciskiem na Hoaxes i Misinformation - Dombrovska, Michaela; Valjentova, Lucie (AUPC Studia ad Bibliothecarum Scientiam Pertinentia, 2023)
The Institute of Czech Language and Library Science of the Faculty of Philosophy and Science of the Silesian University in Opava (Czechia), in cooperation with the Department of Library and Information Science of the Faculty of Philosophy of Comenius University in Bratislava (Slovakia), conducted comparative research on information behavior of university students during the COVID-19 pandemic and related lockdowns. The Czech data collection was made possible within the framework of an internal student grant competition at Silesian University (SGS/2/2021 and SGS/2/2022). In the first phase, data was gathered through online question-naires with open-ended questions emphasizing self-reflective thinking of the respondents. In the second phase, the data was collected through in-depth, semi-structured interviews with selected participants from the first phase. The data collection in Slovakia was supported by the Agency for Research and Development Support under contract APVV-19-0074 and was also part of the project VEGA 1/0360/21 - Social Representations of Ethical Challenges of the Digital Information Revolution. With a particular focus on the area of hoaxes and misinfor-mation, a comparison of the results showed that the experiences of students from different countries are very similar despite the adjusted method, time gap, and different sample size of the respondents.